2019
DOI: 10.1101/835728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampus has lower oxygenation and weaker control of brain blood flow than cortex, due to microvascular differences

Abstract: The hippocampus is essential for spatial and episodic memory but is damaged early in Alzheimer's disease and is very sensitive to hypoxia. Understanding how it regulates its oxygen supply is therefore key for designing interventions to preserve its function. However, studies of neurovascular function in the hippocampus in vivo have been limited by its relative inaccessibility.Here we compared hippocampal and visual cortical neurovascular function in awake mice, using two photon imaging of individual neurons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…We previously demonstrated that inflammasomes contribute to neuronal cell death following ischemic stroke 7 , in part via NF-κB and MAPK signaling 34 . Our present data indicate that chronic cerebral hypoperfusion may also lead to increased expression and activation of NLRP and AIM2 inflammasome receptors in multiple brain areas, especially in the hippocampal region, which is known to be particularly vulnerable to injury following mild ischemia 45 . Cerebral hypoperfusion in the BCAS model used here is known to impact the hippocampus by mechanisms involving ionic imbalance, excitotoxicity, mitochondrial dysfunction and oxidative stress 4648 .…”
Section: Discussionmentioning
confidence: 60%
“…We previously demonstrated that inflammasomes contribute to neuronal cell death following ischemic stroke 7 , in part via NF-κB and MAPK signaling 34 . Our present data indicate that chronic cerebral hypoperfusion may also lead to increased expression and activation of NLRP and AIM2 inflammasome receptors in multiple brain areas, especially in the hippocampal region, which is known to be particularly vulnerable to injury following mild ischemia 45 . Cerebral hypoperfusion in the BCAS model used here is known to impact the hippocampus by mechanisms involving ionic imbalance, excitotoxicity, mitochondrial dysfunction and oxidative stress 4648 .…”
Section: Discussionmentioning
confidence: 60%
“…The effect of vascular differences on BOLD would be expected to be particularly pronounced in cases in which the capillarization of a brain area is sparse like the hippocampus [75]. As an example of when this can be an issue in the hippocampus, Shaw et al [76] compared activation in the CA1 region of the hippocampus with the visual cortex in mice undergoing optogenetic stimulation of glutamatergic neurons. They coupled this stimulation with optical imaging of CBF, CBV and CMRO 2 .…”
Section: Why Does Regional Variability Arise? the Impact Of Regional mentioning
confidence: 99%
“…It remains unclear why the capillary thrombosis is mainly located in the cortex, instead of the striatum and hippocampus. It has been documented that the topological distribution of the capillary network is different throughout the brain to match the regional metabolism ( Shaw et al, 2019 ; Zhang et al, 2019 ). The vascular network shows distinct distribution and density in the cortex, hippocampus and striatum.…”
Section: Discussionmentioning
confidence: 99%